Employing HCl for Pulp Extraction and Its Effect on Viability and Vigor of Cocoa Seeds (Theobroma cacao L.) Variety TSH 858 - Salwa Rajni Fatchurrohman; Fitri Ekawati; Dini Hervani (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Cocoa seeds are classified as recalcitrant and have a pulp layer containing corrosive substances such as abscisic acid; if not properly cleaned, this layer can inhibit the germination process. To date, manual pulp cleaning using scouring ash remains ineffective and time-consuming. An alternative method is chemical treatment, such as using hydrochloric acid (HCl). The application of HCl at specific concentrations has been shown to effectively dissolve and break down the pulp layer attached to the seeds without damaging the seed tissue. This study aims to evaluate the effectiveness of various HCl concentrations for pulp extraction and their impact on the viability and vigor of cocoa seeds of the TSH 858 variety. The research was conducted at the Seed Technology Laboratory of the Faculty of Agriculture, Andalas University, employing a Completely Randomized Design (CRD) with five treatments: 0% HCl (control), 1% HCl, 3% HCl, 5% HCl, and 7% HCl. Each treatment was replicated four times. Data were analyzed using the F-test at a 5% significance level, followed by Duncan's New Multiple Range Test (DNMRT) at the same level if a significant effect was detected. The parameters measured included seed moisture content, germination rate, seedling height, root length, and vigor index. The results indicated that treatment with 5% HCl yielded the best outcomes for seed vigor, particularly in enhancing root length, but had no significant effect on seed viability. Therefore, 5% HCl is effective for extracting cocoa seed pulp without compromising viability and can improve seed vigour by promoting root growth.